Factors Affecting The Incidence of Dengue Hemorrhagic Fever in the Working Area of UPT Puskesmas Medan Johor - Tiara Novia Fajar Aminah; Meutia Nanda (Universitas Ibn Khaldun Bogor, 2023)
Dengue Hemorrhagic Fever is one of the public health problems in Indonesia. In 2022, there were 131,265 cases with 1,183 deaths. The incidence of dengue fever in Medan Johor in 2022 is 186 cases covering the Medan Johor Health Center Working Area of 41 in the last 6 months. The purpose of this study is to analyze the factors that influence the incidence of dengue fever in the working area of the Medan Johor Health Center in 2022. This research is a quantitative research that is observational analytic using a case control study. The case population was 41 respondents and the control was 41 respondents. The sampling technique uses total sampling for case members, and purposive sampling for control members and data analysis techniques use chi square and multivariate tests. The results of the multivariate test showed that the variables that influenced the incidence of DHF were the availability of cover in water reservoirs with pvalue = 0.002<0.05, action variables with pvalue = 0.034<0.05, and attitude variables with pvalue = 0.014.